2004
DOI: 10.1098/rspb.2004.2758
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the desert locustSchistocerca gregaria(Forskål) (Orthoptera: Acrididae: Cyrtacanthacridinae)

Abstract: The locust genus Schistocerca (Stål) has a transatlantic disjunction, which has been controversial for more than a century. Among 50 species within the genus, only one species, the desert locust (S. gregaria Forskål), occurs in the Old World, and the rest occur in the New World. Earlier taxonomists suggested that the desert locust is a migrant from America, but this view was strongly challenged when a large swarm of the desert locust successfully crossed the Atlantic Ocean from West Africa to the West Indies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
71
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 26 publications
8
71
0
1
Order By: Relevance
“…Thus, its phylogenetic position has considerable relevance for biogeographical scenarios. Chapman et al (2000) suggested that Halmenus and Schistocerca were not closely related, while Song (2004) found the two genera to be sister taxa.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, its phylogenetic position has considerable relevance for biogeographical scenarios. Chapman et al (2000) suggested that Halmenus and Schistocerca were not closely related, while Song (2004) found the two genera to be sister taxa.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, the African Schistocerca lineage evolved first, and trans-Atlantic invasions of the New World were facilitated by the ability of these locusts to undertake extreme long-distance flights in very large swarms. This scenario has been called the 'Old World Origin' hypothesis for Schistocerca (Song 2004). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations